When X Shouldn't Mark the Spot: A Crosswalk to a Unified Code of Ethics for Collaboration in the COVID-19 Era. (4th July 2021) - Neal, Sue M.; Travers, Mary Ellen; Brastow, Ian
Abstract : The emergence of COVID-19 as a global pandemic has necessitated the cooperation and collaboration of public health, public administration, and GIS professionals in order to keep the public informed and safe. This paper examines how these three professions' code of ethics reinforce and conflict each other through a content analysis. A crosswalk is developed that identifies critical domains from all three codes of ethics, identifies keywords in these domains and identifies points of conflict and agreement. The crosswalk resolves conflicts and identifies an outcome unified code of ethics for application to COVID-19 data reporting. Observations grounded in each of the domains were then made of all state health department COVID-19 data reporting sites concluding that there were a number of ethical issues observed on the websites. The most frequent violations were found within domains where the ethical codes were divergent. The paper concludes with a proposed model for the future development of other unified codes of ethics for interprofessional collaboration.